Electromagnetic vibration-energy harvesters - Wang, Yufeng (University of Southern California Digital Library (USC.DL), 2016)
This thesis presents microfabricated and miniature electromagnetic vibration-energy harvesters, including theoretical analysis of a mass-spring system, energy harvesters with ferrofluid liquid spring for low resonant frequency, non-resonant energy harvesters based on ferrofluid liquid bearing, new energy-conversion techniques to scavenge energy from rotation induced by vibration, and a diamagnetic suspension system for harvesting energy from human walking motion. ❧ A novel idea of ferrofluid-based suspension is used for a microfabricated vibration-energy harvester to achieve low resonant frequency and high reliability under strong vibration. The microfabricated electromagnetic energy harvester occupying a volume of 18.4 × 11 × 1.7 mm³ (0.3 cc) and weighing 1 gram has a resonant frequency of 340 Hz and can generate an induced electromotive force (EMF) of 0.58 mV with 36 nW power delivered to matched load of 21 Ω at a vibration frequency and acceleration of 320 Hz and 7 g (response to a vibration amplitude of 17 µm), respectively. Resonant frequency can be reduced with less condensed ferrofluid. An energy harvester with 6-layer printed circuit board (PCB) coil plate and water-based ferrofluid as liquid spring has a volume and weight of 17 × 11× 2.5 mm³ (0.47 cc) and 1 gram, respectively. The resonant frequency is reduced to 15 Hz, and EMF of 1.78 mV and power of 176 nW can be delivered to matched load of 4.5 Ω at resonant frequency with acceleration of 3.5 g (response to a vibration amplitude of 3.86 mm). Cylinder magnet array can be employed to increase the fill factor, accordingly, flexible coil array based on parylene is fabricated with MEMS process to wrap around the magnet array. The cylinder energy harvester with a volume of π×52×23 mm³ (1.8 cc) and weight of 5 gram has an resonant frequency around 16 Hz, induced EMF of Vrms =2.57 mV can be generated with 79 nW power output (into 21 Ω load) under 3 g input acceleration at resonant frequency (vibration amplitude of 2.9 mm). ❧ Non-resonant energy harvester is implemented by suspending freely-sliding magnet array over 9-layer microfabricated coil plate with total coil turns and resistance of 675 and 80 Ω, respectively. A prototype non-resonant electromagnetic energy harvester occupying 20.7 × 12 × 4.5 mm³ (1.1 cc) and weighing 2.5 gram can generate an EMF of 170 mV and deliver 90.35 μW power to matched load of 80 Ω under 2 g vibration at 24.5 Hz (response to a vibration amplitude of 0.827 mm). The power under 2 g acceleration at 2 Hz, 3 Hz and 4 Hz are 3.26 μW, 6.29 μW and 8.44 μW, respectively. Folded acrylic spring can be integrated with the frame to harvester energy when the magnet array collides with the frame fixed on the coil plate. The ring effect caused by the employed spring can increase the power at low frequency (2-4 Hz) by 50% compared with the energy harvester without spring. Theoretical model indicates larger power, can be produced with larger movable range of magnet array. The power at low frequency (2-4 Hz) has almost been tripled when the movable range of magnet array is enlarged from 3 mm to 6 mm. High power at low frequency range makes the non-resonant energy harvester suitable to scavenge energy from human walking motion, experiment results show that 7.6 µW and 18.1 µW power can be delivered to a matched load of 80 Ω from walking (2 m/s) and running (3.56 m/s), respectively. ❧ An energy harvester occupying 2.3 cc and weighing 7.5 gram with an eccentric rotor to transfer vibration to rotation has a resonant frequency of 2.4 Hz, and can generate EMF of 91.8 mV and 175 µW power into matched load of 12 Ω from 2.5 g acceleration (corresponding to 110 mm vibrational amplitude). Experiment results show that hundreds of µW power can be produced with the harvester mounted on human body while walking on the treadmill. EMF can also be produced with a spherical magnet rotating in an acrylic tube wrapped by coil. An energy harvester occupying 0.58 cc and weighing 1.3 gram can generate tens of µW level power to matched load of 11 Ω from 2 g acceleration under low frequency (2-4 Hz). The changing of the polarization caused by rotation of the spherical magnet is random which will make the EMF random and reduce the root mean square (rms) of the EMF. The randomness can be reduced by employing a cylinder magnet which can rotate in a box with the direction of the polarization confined in a plane parallel to the vibration direction. An energy harvester occupying 6.75 cc and weighing 2.8 gram can deliver mW level power to matched load of 104 Ω from 2 g acceleration under low frequency (2-4 Hz). ❧ Energy harvester with low resonant frequency can also be achieved by floating a magnet in air with a pair of pyrolytic graphite substrates and an additional magnet on top to counteract the gravity of floating magnet. The novel levitation mechanism allows a low resonant frequency (1-5 Hz) without a heavy proof mass. A subminiature energy harvester weighing 22 gram has a resonant frequency of 3.4 Hz and can generate 11.7 µW from the back of a human walking at 2 m/s. Magnet array with alternating north and south pole can also be floated with this mechanism. A 4.5 gram energy harvester with floating magnet array and PCB coil has a resonant frequency of 4.2 Hz and can produce EMF of 8.29 mV with power of 2.3 µW delivered to matched load of 7.5 Ω under 2 g acceleration at 4.2 Hz.